The influence of nostalgia on serious leisure participation to achieve personal growth and happiness - Low, Shirmin Li Min (2019)
Serious leisure promotes life satisfaction and improves well-being. As a concept, it encompasses both reasons and outcomes for participation. This study looks outside the scope of its innate characteristics and looks at how nostalgia could affect serious leisure participation, and in turn result in personal growth and happiness. 305 responses were collected from serious leisure participants through the completion of a questionnaire. The data was analyzed using confirmatory factor analysis and structural equation modelling. Results showed that nostalgia had a significant positive effect on serious leisure participation. Nostalgia was reported to have indirect effects on personal growth and happiness as well. In addition, serious leisure positively affected personal growth and indirectly affected happiness. These findings will provide a deeper understanding on the relationship between the constructs and aid in widening the extant literature on serious leisure and its outcomes.